Cost-effectiveness of intravenous 5 mg zoledronic acid to prevent subsequent clinical fractures in postmenopausal women after hip fracture: A model-based analysis - Florian Bleibler; Hans-Helmut König (University of Hamburg, Hamburg Center for Health Economics (HCHE), 2016)
Fractures are associated with high economic costs, increased mortality and loss of health related quality of life. Studies have shown that individuals with prior fractures have an increased risk of experiencing subsequent fractures. Therefore secondary fracture prevention appears useful to reduce further fractures in high risk individuals, e.g., in individuals with a prior hip fracture. A clinical trial (HORIZON-RFT) showed that a yearly dose of 5mg intravenous zoledronic acid (IZA) had a fracture-reducing effect in individuals with a prior hip fracture. As to our knowledge no evidence about the cost-effectiveness of IZA is available, the objective of this study is to evaluate the cost-effectiveness of 5mg IZA in women with a previous hip fracture in comparison to no intervention. For this reason a previously published discrete event simulation model which simulates the natural occurrences of different fractures was enhanced. The main enhancements of the model were the inclusion of medication persistence and potential residual treatment effects of IZA. Model input data in terms of epidemiologic, economic and medication effectiveness data was taken from multiple sources. Quality adjusted life years (QALY) were used as effect measure. Costs were considered from a societal perspective for the year 2009. Costs and QALYs were discounted by 3%. As main outcome we calculated the incremental cost-effectiveness ratio ( exteuro/QALY) and constructed cost-effectiveness acceptability curve (CEAC) to represent the parameter uncertainty around our results. In the base-case analysis the model showed an ICER of 11,602 exteuro/QALY with incremental costs and QALYs of 21.8 exteuro and 0.0018762 QALYs, respectively. At ICER thresholds of 12,500 exteuro/QALY and 80,000 exteuro/QALY the CEAC showed a probability for cost-effectiveness of 48% and 93%, respectively. The result of the model suggest that yearly 5 mg intravenous zoledronic acid is a cost-effective intervention in postmenopausal women after a hip fracture.
Keywords: 330; cost-effectiveness; fractures; zoledronic acid; discrete event simulation